Employee performance analysis to increase profitability; Case study at PT XYZ, BEKASI-WEST JAVA - Satria, Budi; Setiawati, Nur Amega (Journal of Economic Development, Environment and People, 2018)
The purpose of this study was to analyze the performance of PT XYS employees engaged in ceramics. Seeing strong business competition, the development of human resources is very important in increasing the productivity of the company. The research was conducted in three divisions namely Plant, Accounting and Finance and Marketing. The results showed that the achievement of the objectives of each Division was quite good / high, especially the Plant division. This is because the SOP that is applied is almost completely implemented, besides that the supervision system is run properly so that it can create a comfortable working atmosphere for employees.